ChemInform Abstract: Synthesis of 5‐Substituted‐1H‐pyrazolo[4, 3‐d]pyrimidin‐7(6H)‐one Analogues and Their Biological Evaluation as Anticancer Agents: mTOR Inhibitors. Issue 47 (6th November 2014) - Reddy, G. Lakshma; Guru, Santosh Kumar; Srinivas, M.; Pathania, Anup Singh; Mahajan, Priya; Nargotra, Amit; Bhushan, Shashi; Vishwakarma, Ram A.; Sawant, Sanghapal D.
Abstract The in vitro anticancer screening of new compounds (III) (20 examples) against human cancer cell lines (HeLa, CAKI‐I, PC‐3, MiaPaca‐2, A549) gives good results.